2003
DOI: 10.1128/iai.71.7.3740-3747.2003
|View full text |Cite
|
Sign up to set email alerts
|

Gingipain RgpB Is Excreted as a Proenzyme in the vimA -Defective Mutant Porphyromonas gingivalis FLL92

Abstract: We have previously shown that the unique vimA (virulence-modulating) gene could modulate proteolytic activity in Porphyromomas gingivalis. Although a reduction in cysteine protease activity was observed in the vimA-defective mutant, P. gingivalis FLL92, compared to that of the wild-type strain, no changes were seen in the expression of the gingipain genes. This result might suggest posttranscriptional regulation of protease expression. To determine whether there was a defect in the translation, transport, or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
1
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(63 citation statements)
references
References 44 publications
8
53
1
1
Order By: Relevance
“…VimA is a putative membrane protein that appears to play a role in virulence regulation in P. gingivalis via gingipain biogenesis (Abaibou et al, 2001;Olango et al, 2003;Vanterpool et al, 2005b). If vimA is part of a pathway(s) that is involved in the maturation and/or activation of the gingipains, then it is likely that VimA could interact with the gingipain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VimA is a putative membrane protein that appears to play a role in virulence regulation in P. gingivalis via gingipain biogenesis (Abaibou et al, 2001;Olango et al, 2003;Vanterpool et al, 2005b). If vimA is part of a pathway(s) that is involved in the maturation and/or activation of the gingipains, then it is likely that VimA could interact with the gingipain.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that inactivation of the vimA gene alters the maturation of the gingipains (Olango et al, 2003;Vanterpool et al, 2005b; Fig. 1).…”
Section: Bioinformatic Analysis Of Vimamentioning
confidence: 99%
See 1 more Smart Citation
“…One-litre cultures of P. gingivalis strains FLL203 and W83 were grown to stationary phase (OD 600 1?5) from actively growing cells. Preparations of whole-cell culture, cell-free medium, cell suspension, vesicles and vesicle-free medium were made as previously reported (Olango et al, 2003). The whole-cell culture (WC) fraction is a sample of the culture after the bacterium has been grown to a specific growth phase.…”
Section: Introductionmentioning
confidence: 99%
“…SDS-PAGE and transfer to nitrocellulose membranes were as described by Vanterpool et al (2006). The blots were probed with antibodies against specific protease domains (Olango et al, 2003) or HagA (generously donated by Ann Progulske-Fox, University of Florida). The secondary antibody was immunoglobulin G (heavy plus light chains)-horseradish peroxidase conjugate (Zymed Laboratories).…”
Section: Introductionmentioning
confidence: 99%